Methods for Three-Dimensional All-Optical Manipulation of Neural Circuits - Ronzitti, Emiliano; Emiliani, Valentina; Papagiakoumou, Eirini (Frontiers in Cellular Neuroscience, 2018)
Optical means for modulating and monitoring neuronal activity, have provided substantial insights to neurophysiology and toward our understanding of how the brain works. Optogenetic actuators, calcium or voltage imaging probes and other molecular tools, combined with advanced microscopies have allowed an “all-optical” readout and modulation of neural circuits. Completion of this remarkable work is evolving toward a three-dimensional (3D) manipulation of neural ensembles at a high spatiotemporal resolution. Recently, original optical methods have been proposed for both activating and monitoring neurons in a 3D space, mainly through optogenetic compounds. Here, we review these methods and anticipate possible combinations among them.